Fatigue crack growth in CFRP-strengthened steel plates. (April 2015) - Colombi, Pierluigi; Fava, Giulia; Sonzogni, Lisa
Abstract: In this paper fatigue crack growth in steel plates reinforced by using carbon fiber reinforced (CFRP) strips is investigated from the experimental, numerical and analytical point of view. Single edge notched tension (SENT) specimens were strengthened with different reinforcement configurations and tested at a stress ratio R of 0.4. Different initial damage levels were considered and the experimental results showed that the reinforcement application can effectively reduce the crack growth rate and significantly extend the fatigue life. Numerical models (finite elements) were also developed to evaluate the stress intensity factor (SIF) and the crack opening displacement (COD) profile. Based on the numerical results, an analytical model was proposed to predict the fatigue crack growth rate and the fatigue crack growth curves. The analytical results are validated by comparing the fatigue crack growth curves to the experimental ones.